Detection technologies for RNA modifications - Zhang, Yan; Lu, Liang; Li, Xiaoyu (Experimental & molecular medicine, 2022)
To date, more than 170 chemical modifications have been characterized in RNA, providing a new layer of gene expression regulation termed the ‘epitranscriptome’. RNA modification detection methods and tools advance the functional studies of the epitranscriptome. According to the detection throughput and principles, existing RNA modification detection technologies can be categorized into four classes, including quantification methods, locus-specific detection methods, next-generation sequencing-based detection technologies and nanopore direct RNA sequencing-based technologies. In this review, we summarize the current knowledge about these RNA modification detection technologies and discuss the challenges for the existing detection tools, providing information for a comprehensive understanding of the epitranscriptome. RNA modifications: Comparing detection tools Improved methods for detecting chemical modifications of RNA will help to understand the epitranscriptome, the collection of RNA modifications in a cell. Chemical modifications to RNA molecules do not alter the sequence, but can nonetheless greatly affect RNA function. More than 170 RNA modifications have been discovered over the past 60 years and their effects are analogous to epigenetic modifications of DNA. Xiaoyu Li and co-workers at Zhejiang University School of Medicine in Hangzhou, China, reviewed existing tools for detecting RNA modifications. These tools, which are developed based on the inherent chemical properties of RNA modifications, vary in sensitivity, quantification, specificity and accuracy. The researchers also summarize the recent progress in nanopore direct RNA sequencing based detection technology and are optimistic that future advances will enable detection of different modifications simultaneously in the single molecules.